John Paul II’s Charter of the Rights of the Family. The Social Dimension of Human Rights in Light of Natural Law - Carlos Alberto Gabriel Maino (Warszawskie Studia Teologiczne)
The teachings of Saint John Paul II in connection with the family in general and the Charter of the Rights of the Family in particular focus on the social dimension of human rights in the hermeneutic key of natural law and the common good. The author of the article explains why such an approach is necessary and what its importance is for an appropriate philosophy of human rights.